Gratitude and Resilience of Recipients of Direct Cash Assistance from Village Funds - Setyaningrum, Dyah Titi; Sindriana, Sahrul (Journal of Health and Behavioral Science, 2023)
Gratitude and resilience play significant roles among families categorized as pre-prosperous, who are unable to meet the minimum basic needs in terms of clothing, food, shelter, and healthcare. They are part of the recipients of the Village Fund Direct Cash Assistance Program (BLTDD), aimed at assisting them in meeting their livelihood needs amidst the pandemic crisis. Being resilient individuals is crucial for these pre-prosperous families to remain resilient and maintain a quality life despite challenging circumstances. Initial interviews revealed that gratitude for the life they lead contributes to the respondents' ability to navigate their lives. This study aims to understand the role of gratitude in resilience among BLTDD beneficiaries. It is an inductive study utilizing quantitative methods involving 86 aid recipients. The gratitude measurement tool was constructed based on McCullough, Emmons, and Tsang's gratitude theory (2002), while the resilience measurement tool was based on Reivich and Shatte's resilience theory (2002). The validity of the measurement tools was analyzed using confirmatory factor analysis with factor loading scores ≥ 0.5, and reliability was assessed using Cronbach's α coefficient, where the gratitude measure scored 0.934 and resilience 0.884. The research results indicate a P Value < 0.001 and an R2 value of 0.180. Thus, the conclusion drawn from this research is that there is a significant influence of the gratitude variable on resilience, accounting for 18.1%